Repetitive DNA Sequences in the Human Y Chromosome and Male Infertility - Xu, Yong; Pang, Qianqian (Frontiers in Cell and Developmental Biology, 2022)
The male-specific Y chromosome, which is well known for its diverse and complex repetitive sequences, has different sizes, genome structures, contents and evolutionary trajectories from other chromosomes and is of great significance for testis development and function. The large number of repetitive sequences and palindrome structure of the Y chromosome play an important role in maintaining the stability of male sex determining genes, although they can also cause non-allelic homologous recombination within the chromosome. Deletion of certain Y chromosome sequences will lead to spermatogenesis disorders and male infertility. And Y chromosome genes are also involved in the occurrence of reproductive system cancers and can increase the susceptibility of other tumors. In addition, the Y chromosome has very special value in the personal identification and parentage testing of male-related cases in forensic medicine because of its unique paternal genetic characteristics. In view of the extremely high frequency and complexity of gene rearrangements and the limitations of sequencing technology, the analysis of Y chromosome sequences and the study of Y-gene function still have many unsolved problems. This article will introduce the structure and repetitive sequence of the Y chromosome, summarize the correlation between Y chromosome various sequence deletions and male infertility for understanding the repetitive sequence of Y chromosome more systematically, in order to provide research motivation for further explore of the molecules mechanism of Y-deletion and male infertility and theoretical foundations for the transformation of basic research into applications in clinical medicine and forensic medicine.